The Impact of Ethnic Politics on Javanese Muslims in Malaysia: Integration, Identity, and Political Leadership - Arik Dwijayanto; Teguh Ansori; Intan Farhana Binti Saparudin; Mohd Shafiq Bin Sahimi (Journal of Social Transformation and Regional Development, 2024)
This article examines the impact of ethnic politics on Javanese migrants and their descendants in Malaysia, focusing on their social, economic, and political realities. It explores the historical context of ethnic politics in Malaysia and how it has shaped the experiences of the Javanese community, from their integration into Malay society to the emergence of a Malay-Javanese middle class. The article argues that ethnic-based policies, such as the New Economic Policy (NEP), have provided opportunities for the Javanese to gain citizenship rights and participate in Malaysia’s development while also contributing to the strengthening of identity politics. It highlights the political role of Javanese Muslim leaders, who have risen to prominent positions within the United Malays National Organisation (UMNO) and the government. The article draws on historical sources, government policies, and scholarly works to provide a comprehensive analysis of the Javanese experience in Malaysia amidst the complexities of ethnic politics. It concludes by emphasising the need to understand the dynamics of ethnicity and religion in Malaysia’s nation-building process and their impact on minority communities like the Javanese. The article contributes to the ongoing debate on leadership, ethnicity, and representation in contemporary Malaysia while offering insights into the challenges and opportunities faced by migrant communities in multi-ethnic societies.